3D Digital Libraries and Their Contribution in the Documentation of the Past - Ioannides, Marinos; Davies, Rob; Chatzigrigoriou, Pavlos; Papageorgiou, Eirini; Leventis, Georgios; Nikolakopoulou, Vasiliki; Athanasiou, Vasilis (My University, 2017)
From the ancient library of Alexandria 2300 years ago, the objectives of the collection of information has a common fundamental base: to gather, preserve, and promote knowledge, thus helping in the intellectual and cognitive evolution of humanity. Today, the information revolution has given the ability to scientists, educators, researchers, and individuals not only to use a variety of digital libraries as an information source but also to contribute to these libraries by uploading data that they create, leading to a massive production of knowledge that we need to verify, manage, archive, preserve, and reuse. Cultural heritage data is a category in digital libraries that needs much attention, because of its crucial role in helping us to interact with the past and learn, promote, and preserve our cultural assets. Digital documentation of tangible and intangible heritage, data formats and standards, metadata and semantics, Linked Data, crowdsourcing and cloud, use and reuse of data, and copyright issues are the rising challenges that we try to address in this chapter, through literature review and best practice examples. At the end of this analysis, this chapter tries to predict the near future of digital heritage libraries, where 3D digital assets will be part of augmented, virtual, and mixed reality experiences.
Keywords: Digital libraries; Digital documentation; 3D reconstruction; Semantic annotation; Ontology; 3D library; Crowdsourcing